Phosphoregulation of Kinesins Involved in Long-Range Intracellular Transport - Kumari, Diksha; Ray, Krishanu (Frontiers in Cell and Developmental Biology, 2022)
Kinesins, the microtubule-dependent mechanochemical enzymes, power a variety of intracellular movements. Regulation of Kinesin activity and Kinesin-cargo interactions determine the direction, timing and flux of various intracellular transports. This review examines how phosphorylation of Kinesin subunits and adaptors influence the traffic driven by Kinesin-1, -2, and -3 family motors. Each family of Kinesins are phosphorylated by a partially overlapping set of serine/threonine kinases, and each event produces a unique outcome. For example, phosphorylation of the motor domain inhibits motility, and that of the stalk and tail domains induces cargo loading and unloading effects according to the residue and context. Also, the association of accessory subunits with cargo and adaptor proteins with the motor, respectively, is disrupted by phosphorylation. In some instances, phosphorylation by the same kinase on different Kinesins elicited opposite outcomes. We discuss how this diverse range of effects could manage the logistics of Kinesin-dependent, long-range intracellular transport.